LO11: Influence of fear of falling on return to emergency department and further falls in community-dwelling elderly presenting for minor trauma. (May 2019) - Lanoue, M.; Sirois, M.; Worster, A.; Perry, J.; Lee, J.; Daoust, R.; Hegg, S.; Carmichael, P.; Émond, M.
Abstract : Introduction : According to WHO, one third of patients aged ≥65 fall every year. Those falls account for 25% of all geriatric emergency department (ED) visits. Fear of falling (FOF) is common in older patients who sustained a fall and is associated with a decline in mobility and health issues for patients. We hypothesized that there is an association between FOF and return to ED (RTED) and future falls.Objective : To assess the relation between FOF and RTED and subsequent falls in older ED patientsMethods : This research was conducted as part of the Canadian Emergency Team Initiative in elderly (CETIe) multicenter prospective cohort study from 2011 to 2016.Participants : Patients 65 years or older were assessed and discharged from ED following a minor trauma. They had to be independent in all basic activities of daily living and being able to communicate in English or French.Measures : Primary outcome was RTED and secondary outcome was subsequent falls. Both were self-reported at 3 and 6 months. Patients were stratified according to Short Falls Efficacy Scale International (SFES-I) score, assessing FOF in different situations. A total score is calculated to determine the mild, moderate or severe level of FOF. Previous falls and TUG were used to evaluate patients' mobility. OARS, ISAR and SOF were used to evaluated patient frailty. Descriptive statistical were performed and multiple regression were performed to show the association between SFES-1 score and outcomes.Results : FOF was measured in 2899 participants, of which 2214 participated at the 3 months follow-up and 2009 participated at the 6 months follow-up. Odds Ratio (OR) of return to ED at 3 months was 1.10 for moderate FOF and 1.52 for severe FOF (Type 3 test p = 0.11). At 6 months, OR was 1.03 for moderate FOF and 1.25 for severe FOF (Type 3 test p = 0.63). OR of subsequent fall at 3 months was 1.80 for moderate FOF and 2.18 for severe FOF (Type 3 test p < 0.001). At 6 months, OR of subsequent fall was 1.63 for moderate FOF and 2.37 for severe FOF (Type 3 test p < 0.001).Conclusion : The multicenter cohort study showed that severe fear of falling is strongly associated with subsequent falls over the next 6 months following ED discharge, but not significantly associated with return to ED episodes. Further research should be done to analyze the association between severe FOF and RTED.